Readiness for change of school principals in the implementation of the Merdeka Mengajar platform - Sari, Rika Yohana; Yahya, Yahya; Rusdinal, Rusdinal; Sabandi , Ahmad (Indonesian Research Journal in Education |IRJE|, 2025)
The principal’s readiness for change is crucial in supporting schools to produce superior students. However, observations at several schools indicate that principals often show limited physical and non-physical development in their institutions. Implementing leadership policies related to innovation, creativity, and technology has been suboptimal, and there is a lack of genuine planning for organizational improvement. This research employed a qualitative descriptive method with data collected through interviews. Findings revealed that implementing the Merdeka Mengajar Platform at Gugus III SD Negeri Kuranji reflected a superficial understanding without in-depth learning, resulting in minimal impact on organizational progress. Challenges included inadequate principal competence in using the platform, low motivation due to approaching retirement, and insufficient time to learn because of professional and personal duties. Consequently, the lack of readiness for change hinders teacher development, limits innovation in teaching, and reduces the effectiveness of reporting and evidence-based practices.